Spatiotemporal variability at seasonal and interannual scales of terrestrial water variation over Tibetan Plateau from geodetic observations - Yuanjin Pan; Xiaohong Zhang; Jiashuang Jiao; Yixin Xiao (Geo-spatial Information Science)
In the context of ongoing global climate warming, researchers have observed an intricate relationship between the variability of Terrestrial Water Storage (TWS) on the Tibetan Plateau (TP) and climate anomalies. In this study, we utilize a combination of Global Navigation Satellite System (GNSS), Gravity Recovery and Climate Experiment (GRACE), and precipitation data to investigate the response of TWS on the TP to extreme climate changes, with a focus on seasonal and interannual variations. Our findings reveal that the first Common Mode Component (1st CMC) extracted from GNSS coordinate time series exhibits strong interannual fluctuations. Additionally, both GNSS and GRACE-inferred TWS demonstrate noticeable anomalous changes during the 2015/2016 period. The estimated periods of the 1st CMC of GNSS and GRACE-inferred TWS are approximately 5 and 7 years, respectively. Both reach a minimum during the extreme climate event in 2015/2016. Furthermore, we investigate the spatial variation of summer precipitation before and after the extreme drought event on the TP. It reveals that the inflection point of TWS occurs approximately 1 year prior to the drought event, suggesting a consistent spatial propagation process between precipitation and TWS. This indicates that the changes of TWS during this drought event were primarily influenced by precipitation. Finally, we evaluate the response of 12 sub-basins on the TP to the drought event that occurred in 2015/2016. The regions experiencing significant abnormal fluctuations in TWS are mainly located in inner and northeastern plateau. These regions show rapid upward changes in the TWS and demonstrate a strong spatial consistency with summer precipitation.